2014
DOI: 10.4236/cweee.2014.34018
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Develop the Integration of the Environmental Management System with Other Standardized Management Systems

Abstract: Traditionally the global management system of an organization is frequently split into a number of individual management systems that are defined and implemented according to specific management systems standards (MSSs) as well as managed independently. The individual implementation of MSSs is an option that leads to several inefficiencies and sub-optimization of the global management system of an organization. As referred by ISO [1] the interested parties' requirements increase. A more effective and efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(37 reference statements)
0
4
0
1
Order By: Relevance
“…Integration is a very important feature of research and is debatable [32,39]. The integration of knowledge is an important process in organizations [40][41][42]. The novelty of knowledge management in integrated management systems in construction companies has been shown in Table 2.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…Integration is a very important feature of research and is debatable [32,39]. The integration of knowledge is an important process in organizations [40][41][42]. The novelty of knowledge management in integrated management systems in construction companies has been shown in Table 2.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…The recurring themes addressed in the mainstream literature within the IMSs scientific domain reported the limitations of the lack of integration (Almeida et al , 2014; Domingues et al , 2012, 2015), enabled the identification of critical success factors (Almeida et al , 2014; Oliveira, 2013) and dissected the guidelines and strategies for integration of MSs (Oliveira, 2013; Rebelo et al , 2014a). In addition, several authors proposed some contributions on the proper design of IMSs (Garengo and Biazzo, 2013; Manzanera et al , 2014; Rebelo et al , 2014b; Zeng et al , 2007), on the factors that impact the integration level attained (Bernardo et al , 2011, 2012) and suggested integration levels or degrees (Bernardo et al , 2009; J酶rgensen et al , 2006; J酶rgensen, 2008; Sampaio et al , 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Company should therefore potentiate for each stage: Plan, Do, Check, Act a careful and methodical analysis of the differences that effectively can be observed in terms of standards requirements under involved equivalent clauses and for each phase and at each stage of development of the SIG-QES, according to the model of Figure 3 [21,36,37], to ensure its compliance and evidence of it, in full conformity. First of all, the definition, approval and communication of the Integrated Management Policy, a common requirement to the different normative references, must take into account and be consistent with the Mission and Vision of the organization-these supported on a strategy and specific objectives which in turn support the implementation of that policy and its consequent effectiveness.…”
Section: Model To Support the Development Of The Imsmentioning
confidence: 99%